Human immunodeficiency viruses in patients attending a sexually transmitted disease clinic in London, 1982-7. Issue 6671 (18th February 1989) - Loveday, C.; Pomeroy, L.; Weller, I. V.; Quirk, J.; Hawkins, A.; Williams, H.; Smith, A.; Williams, P.; Tedder, R. S.; Adler, M. W.
Abstract : OBJECTIVE--To determine the prevalence of infection with the human immunodeficiency virus (HIV) in all patients attending a London sexually transmitted disease clinic over four weeks at the end of 1987 and to see how it varied from that in similar samples studied between 1982 and 1986. DESIGN--Anonymous testing of serum samples from consecutive heterosexual and homosexual patients having routine serological investigations for syphilis. Testing was for anti-HIV-I, anti-HIV-II, and hepatitis B core antibody (anti-HBc) and P24 antigen. Age, nationality, sexual orientation, and past sexually transmitted diseases were recorded for each patient. Gonorrhoea rates by quarters were analysed among homosexual and bisexual men and heterosexual men and women from 1981 to 1987. SETTING--Outpatient department of genitourinary medicine. PATIENTS--A total of 1074 patients attending consecutively for syphilis serology. Thirty five homosexual and bisexual men were excluded (these were regular attenders as part of a prospective study of the natural course of HIV infection). MEASUREMENTS AND MAIN RESULTS--The prevalence of anti-HIV-I in homosexual and bisexual men in 1987 was 25.6% (64/250). Results in the same clinic population between 1982 and 1984 had shown a rise in prevalence, which flattened out in 1985-6 and continued at that level. Among heterosexual attenders in 1987 the prevalence of anti-HIV-I was 1% (women 4/412; men 4/377), which contrasted with a prevalence of 0.5% (women 2/395; men 3/757) in January 1986. One homosexual man was seropositive for anti-HIV-II and seronegative for anti-HIV-I. Among homosexual and bisexual men the rate of gonorrhoea had declined by an average of 2.7% a year since 1981, such that by 1987--and for the first time in the clinic--there was no significant difference in the rates between these men and heterosexual men and women. CONCLUSIONS--The appearance of HIV-I infection among heterosexuals indicates a need for more aggressive education programmes and intervention strategies along the lines adopted for homosexual men. Surveillance for HIV-II infection is needed to provide information for future policy in national screening programmes.